URGENCE OF IMPLEMENTATION OF THE IMMIGRATION FORENSIC SECTION AS A PREVENTIF EFFORTS: CASE STUDIES OF MALAYSIAN FAKE PASSPORT EXAMINATION ON THE NAME OF SELVARASA KRISNHA PILLAI - M. Alvi Syahrin; Yusuf Sadewa (Polteknik Imigrasi, 2018)
Increased flow of traffic in and out of Indonesia, creates a variety of immigration crime rates. Passport forgery as a crime committed by changing, changing part or all of a passport or using false information to receive a passport has now become a serious problem. At present, almost all fake passport verification processes are carried out at the Immigration Forensic Laboratory at the Directorate of Immigration Intelligence. The formulation of the problems examined in this paper are (1) how does the function of the Immigration Forensic Laboratory function function as a preventive measure? (2) How does the function of the Immigration Forensic Laboratory function function in handling Malaysian national fake passport inspection cases on behalf of Selvarasa Krishna Pillai ?. Based on the results of the study, it can be seen that the Immigration Forensic Laboratory Section plays a role in implementing immigration preventive efforts. Preventive efforts carried out by the Immigration Forensic Laboratory Section include training in fake passport detection techniques, information exchange with other countries, and the dissemination of the latest information regarding immigration. Examination of fake immigration documents The Immigration Forensic Laboratory section plays a role in carrying out its functions by conducting fake passport checks in this case.